On Dirichlet's principle and problem - Åhag, Per; Cegrell, Urban; Czyz, Rafal (Mathematica Scandinavica, 2012)
The aim of this paper is to give a new proof of the complete characterization of measures for which there exists a solution of the Dirichlet problem for the complex Monge-Ampere operator in the set of plurisubharmonic functions with finite pluricomplex energy. The proof uses variational methods.